Perceptions of mindfulness to pregnant women with gestational diabetes: an exploratory qualitative Portuguese study - Seixinho, Sandra; Presado, Maria Helena (Frontiers in Global Women's Health, 2025)
IntroductionGestational diabetes (GD) significantly impacts maternal well-being, influencing both physical and psychological health. Non-pharmacological interventions, such as mindfulness, have emerged as potential nursing strategies to promote positive experiences during pregnancy. This study investigates the perceptions of mindfulness in pregnant women diagnosed with GD, with the aim of analyzing the perceptions of pregnant women about mindfulness. The research question was defined as “What are the perceptions of mindfulness to diabetic pregnant women?”.MethodsAn exploratory qualitative approach was employed to deeply explore the perceptions of pregnant women regarding mindfulness. Seven pregnant women with GD, who met specific inclusion criteria, were intentionally selected and invited to participate in the study. Data were collected through semi-structured interviews and analyzed using Bardin's content analysis method.ResultsParticipants perceived mindfulness as beneficial in several areas. Improvements in general well-being, physical and psychological health, better interpersonal relationships, increased relaxation, greater preparation for childbirth, and strengthened confidence during the transition to motherhood.DiscussionThe results indicate that mindfulness is perceived by pregnant women with GD as a valuable tool for improve their well-being and facilitating a smoother transition to motherhood. The study highlights the importance of incorporating mindfulness into nurse care, especially in the context of high-risk pregnancies. The results suggest that mindfulness can be integrated into nursing practices to more effectively support pregnant women. Further research is recommended to explore the broader implications of mindfulness in high-risk pregnancy care.